Preexisting white matter hyperintensity lesion burden and diagnostic certainty of transient ischemic attack - NAGY, MUHAMMAD (J Stroke Cerebrovasc Dis, 2019)
GOALS: There are no validated biomarkers that allow for reliable distinction between TIA and other transient neurological symptoms that mimic TIA. We sought to determine whether the degree of preexisting white matter hyperintensity (WMH) lesion burden relates to the diagnostic certainty of TIA in a cohort of patients presenting with transient neurological symptoms. MATERIALS AND METHODS: We retrospectively analyzed 144 consecutive patients with available brain MRI to quantify and normalize the WMH volume for brain atrophy (aWMHV). We first stratified subjects to probable (n=62) versus possible (n=82) TIA as per existing guidelines. Receiver-operating characteristic curves were used to determine a critical aWMHV-threshold (7.8 mL) that best differentiated probable from possible TIA. We then further stratified patients with possible TIA to likely (n=52) versus unlikely (n=30) TIA after independent chart review and adjudication. Finally, multivariable logistic and multinomial regression was used to determine whether the defined aWMHV independently related to probable and likely TIA after adjustment for pertinent confounders. FINDINGS: With the exception of age (p<0.001) and use of antiplatelets (p=0.017) baseline characteristics were similar between patients with probable, likely, and unlikely TIA. In the fully adjusted multinomial model, the aWMHV cut-off >7.8 mL (OR 3.8, 95%-CI 1.3–10.9, p=0.012) was significantly more frequent in patients with a probable TIA as compared to those with an unlikely TIA diagnosis. CONCLUSION: We provide proof-of-principle that WMH may serve as a neuroimaging marker of diagnostic certainty of TIA after neurological workup has been completed.